Clinical leadership and organizational climate on the performance of healthcare personnel mediated by quality of work life - Siswaty, Donna Shandra; Meilani, Yohana F. Cahya Palupi (Institute of Computer Science (IOCS), 2023)
The performance of health workers is one of the main factors influencing hospital improvement. The better the healthcare personnel's performance, the more patients will feel satisfied and this can influence the patient's interest in returning to the hospital. There is a decrease in the number of patients at the xyz military hospital from 2017-2023 and the number of complaints is 5-10 cases every month. This research aims to determine the influence of clinical leadership and organizational climate on job performance which is mediated by quality of work life. In this research, the cross-sectional method was used to obtain quantitative data from physical questionnaires. This research is a census study which takes the entire population as the research sample, namely health workers at the XYZ military hospital who have worked for 3 months with a total of 150 people and then the data analyzed using SmartPLS. The research results showed there is a positive and significant influence between clinical leadership and organizational climate on the quality of work life, organizational climate on job performance, and quality of work life on job performance. Quality of work life has also been proven to mediate clinical leadership and organizational climate on job performance.